A new Russian regulatory dispersion model "MEAN" for calculation of mean annual concentrations and its meteorological pre-processor. (1st January 2000) - Genikhovich, E.L.; Gracheva, I.G.; Groisman, P.Ya.; Khurshudyan, L.H.
A new Russian regulatory dispersion model "MEAN" is based on integration of the analytical expressions which approximate the numerical solution of the advection-diffusion equation (ADE). The meteorological preprocessor of this model uses routine information from the national meteorological network to estimate and process necessary dispersion parameters. Turbulent fluxes of the sensible heat calculated using this preprocessor are compared with those measured using the eddy-correlation technique or estimated from profile measurements. Results of the validation of this model are also presented.